1998
DOI: 10.1159/000026185
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Parkinson’s Disease in an Australian Population

Abstract: A prevalence study of Parkinson’s disease (PD) was conducted in the rural town of Nambour, Australia. There were 5 cases of PD in a study population of 1207, yielding a crude prevalence ratio of 414 per 100,000 (95% confidence interval; 53–775). We performed a separate case-control study involving 224 patients with PD and 310 controls from South East Queensland and Central West New South Wales, to determine which factors increase the risk for PD in Australia. A positive family history of PD was the strongest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 30 publications
(48 reference statements)
6
128
1
Order By: Relevance
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
See 4 more Smart Citations
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
“…Two reported statistically imprecise ORs at 10.9 (95% CI 1.8-67.5) [355] and 8.7 (95% CI 1.5-52.0) [312]. Of the remaining 25 studies that examined well water in relation to PD, three reported a decreased risk [131,141,146], whereas the others found no association [136, 143-145, 154, 289, 292, 293, 300, 302, 307, 310, 311, 314, 315, 321, 325, 350, 351, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 99%
See 3 more Smart Citations